Numerical estimation of 10000 years later equilibrium ice sheet profile in the Shirase Glacier drainage basin, East Antarctica - Shuji Fujita; Norikazu Ikeda; Nobuhiko Azuma; Takeo Hondoh; Shinji Mae (National Institute of Polar Research, 1991)
Recent observations show that the ice sheet in the Shirase Glacier drainage basin, East Antarctica, is thinning. If the observed thinning is assumed to be a transitional process in which the ice sheet is adjusting to the present climate, an equilibrium ice sheet profile which adjusts to the present climate would provide us with information for understanding the present behavior of the ice sheet. The equilibrium ice sheet profile was estimated by using a three-dimensional non-steady state ice sheet model. Estimations were carried out with data based on observations of bedrock topography, surface elevation, accumulation rate and surface temperatures, and their extrapolation for areas where there is no field data. And the equilibrium ice sheet profile against various parameters, e.g. surface temperatures, accumulation rate and geothermal heat flux, was investigated. Results of the calculation showed that an almost stationary state of the ice sheet was achieved after (10)^4 model years when started from the present profile of the ice sheet. The equilibrium ice sheet profile depended on bedrock topography and tested parameters sensitively, but the calculations indicated that ice-thickness tend to decrease in the middle-stream region in general. It was also revealed that the ice sheet in the vicinity of the Yamato Mountains was relatively stable even if the parameters were changed.